Matrix Metalloproteinase-12 Is Required for Granuloma Progression - Mohan, Arjun; Neequaye, Nicole; Malur, Anagha; Soliman, Eman; McPeek, Matthew; Leffler, Nancy; Ogburn, David; Tokarz, Debra A.; Knudson, Warren; Gharib, Sina A.; Schnapp, Lynn M.; Barna, Barbara P.; et al. (Frontiers in Immunology, 2020)
Background: Sarcoidosis is a chronic inflammatory disease of unknown cause characterized by granuloma formation. Mechanisms for chronic persistence of granulomas are unknown. Matrix Metalloproteinase-12 (MMP12) degrades extracellular matrix elastin and enables infiltration of immune cells responsible for inflammation and granuloma formation. Previous studies report increased MMP12 in sarcoidosis patients and association between MMP12 expression and disease severity. We also observed elevated MMP12 in our multiwall carbon nanotube (MWCNT) murine model of granulomatous inflammation. Here we hypothesized that MMP12 is important to acute and late phases of granuloma pathogenesis. To test this hypothesis, we analyzed granulomatous and inflammatory responses of mmp12 KO mice at 10 (acute) and 60 days (late) after MWCNT instillation. Methods: C57BL/6 (wildtype) and mmp12 KO mice underwent oropharyngeal instillation of MWCNT. Lungs were harvested at 3, 10, 20, and 60 days post instillation for evaluation of MMP12 expression and granulomatous changes. Bronchoalveolar lavage (BAL) cells were analyzed 60 days after MWCNT instillation for expression of mediators thought to play a role in sarcoid granulomatosis: peroxisome proliferator-activated receptor-gamma (PPARγ), interferon-gamma (IFNγ), and CCL2 (MCP-1). Results: Pulmonary granuloma appearance at 10 days after MWCNT instillation showed no differences between wildtype and mmp12 KO mice. In contrast, by 60 days after MWCNT instillation, mmp12 KO mice revealed markedly attenuated granuloma formation together with elevated PPARγ and reduced IFNγ expression in BAL cells compared to wildtype. Unexpectedly, mmp12 KO mice further demonstrated increased alveolar macrophages with increased CCL2 at 60 days. Conclusions: The striking reduction of granuloma formation at day 60 in mmp12 KO mice suggests that MMP12 is required to maintain chronic granuloma pathophysiology. The increased PPARγ and decreased IFNγ findings suggest that these mediators also may be involved since previous studies have shown that PPARγ suppresses IFNγ and PPARγ deficiency amplifies granuloma formation. Interestingly, a role of MMP 12 in granuloma resolution is also suggested by increases in both macrophage influx and CCL2. Overall, our results strongly implicate MMP12 as a key factor in granuloma persistence and may represent an attractive therapeutic target in pulmonary sarcoidosis